The stranger - Welles, Orson, 1915-1985; Veiller, Anthony, 1903-1965; Spiegel, Sam; Robinson, Edward G., 1893-1973; International Pictures Inc. ([United States] : International Pictures Inc., 1946)
Charles Rankin is a respectable Connecticut professor about to marry the daughter of a United States Supreme Court justice. However, he hides a terrible secret, since his real identity is that of Franz Kindler, responsible for numerous crimes during the Nazi holocaust. On the other hand, Wilson, belonging to the War Crimes Commission, tracks him down through a comrade of his, Meinike, who is able to rat him out. Rankin, faced with the possibility of his facade being exposed and ending his peaceful existence, ends the life of his former comrade by hiding his corpse deep in the woods. The only clue left for Wilson is his fascination with vintage clocks.--
Edward G. Robinson (Wilson), Loretta Young (Mary Longstreet), Orson Welles (Prof. Charles Rankin), Philip Merivale (Judge Longstreet), Richard Long (Noah Longstreet), Byron Keith (Dr. Jeff Lawrence), Billy House (Mr. Potter), Konstantin Shayne (Meinike), Martha Wentworth (Sara), Isabel O'Madigan (Mrs. Lawrence)
Story, Victor Trivas ; director of photography, Russell Metty ; editor, Ernest Nims ; music, Bronislaw Kaper.
In English or Spanish.
Nomination for Best Screenplay, Original Story - Oscars.
Golden Lion Nomination - Venice Film Festival.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed June 17, 2022)
Keywords: War criminals -- Drama; Nazi hunters -- Drama; Fugitives from justice -- Drama; Impostors and imposture -- Drama; Motion pictures; Fiction films; Drama; Feature films; Streaming video